Efficacy and safety of a novel CD19, CD22 dual-targeted fully human loop bi-CAR-T for the treatment of relapsed/refractory B cell non-Hodgkin lymphoma - Hanyu Wang; Gaoxiang Wang; Tongjuan Li; Peiling Zhang; Zekai Mao; Hui Luo; Xiaojian Zhu; Dengju Li; Jianfeng Zhou; Xiaoxi Zhou; Liang Huang (Journal of Translational Medicine)
Abstract Background Chimeric antigen receptor (CAR) T-cell therapies targeting CD19 have demonstrated promising efficacy in treating refractory or relapsed B-cell malignancies. Nonetheless, challenges such as antigen escape-mediated relapse and toxicities, including cytokine release syndrome (CRS) and neurotoxicity, may impede their clinical application. Methods In this study, we developed a fully human, bivalent loop bi-CAR-T targeting both CD19 and CD22 (CT120). We conducted an open-label, single-center, single-arm phase I/II trial to evaluate the efficacy and safety of CT120 in patients with relapsed or refractory B-cell non-Hodgkin lymphoma (NHL). Results The overall response rate (ORR) was 65.2%, with 56.5% of patients achieving a complete response. The median progression-free survival (PFS) was 23.95 months, and the median overall survival (OS) was not reached. The 12-month PFS rate was 54.66%, and the 12-month OS rate was 77.34%. The 24-month PFS rate was 49.69% and the 24-month OS rate was 72.51%. Prognostic factors for poorer outcomes included bulky mass, high international prognostic index (IPI), multiple extranodal lesions, or MYD88 mutation. No loss of CD19/CD22 expression was observed in patients with relapse. Grade 3 or higher CRS occurred in only one patient (4.3%), and no immune effector cell-associated neurotoxicity syndrome (ICANS) was seen. Notably, we observed both early and late immune effector cell-associated hematotoxicity (ICAHT) following CT120 infusion. Late-onset neutropenia (after day 30) occurred in 78.3% of patients, and severe anemia was correlated with worse prognosis. Conclusions Overall, CT120 infusion is effective, safe, and reliable for reducing antigen escape-related relapse in patients with relapsed or refractory NHL. Trial registration Chinese Clinical Trial Registry (ChiCTR), ChiCTR2000038641). Registered 26 September 2020, https://www.chictr.org.cn/showproj.html?proj=61780 .